Genetic aspects of autosomal dominant late onset cerebellar ataxia. Issue 6 (December 1981) - Harding, A E
Abstract : The genetic features of eight families with autosomal dominant late onset cerebellar ataxia with randomly distributed associated clinical features are described. The ratio of affected to unaffected offspring of affected subjects was not significantly different from 1:1. The mutant gene was fully penetrant when cases who died before the period of risk of developing the disease were excluded. The proportion of new mutants with this disorder appears to be low. Biological fitness was not impaired. Affected females tended to have large families than affected males. The ages of onset of females and males were not significantly different, but the offspring of affected males had earlier ages of onset and death than those of affected females. A cumulative age of onset curve is presented which should aid genetic counselling of subjects at risk and their children.